ENERGY EFFICIENCY IMPROVEMENT IN GEOTHERMAL POWER PLANT WITH THE APPLICATION OF LOAD-BASED GAS REMOVAL SYSTEM AND COOLING WATER PUMP CONTROL SYSTEM - Wibisono
From a thermodynamic perspective, the operation of a Geothermal Power Plant (GPP) follows the Rankine cycle. Efficient electricity generation is achieved through the conservation of energy (enthalpy) of steam from the well to the generator, setting low condensation pressure to achieve maximum energy conversion in the turbine, and minimal electricity consumption (house-load). In almost all GPPs, condensation (condenser) pressure is maintained by the vacuum ejector, which absorbs the accumulation of Non-Condensable Gas (NCG), namely CO2 and H2S. Condensation effectiveness relies heavily on the availability of cooling water, which depends on the performance of the cooling water circulation pump. In general, GPPs are designed to work on base-load (100% capacity); therefore, the performance of supporting equipment such as ejectors and pumps is not sensitive to fluctuations in generation loads or changes in NCG content (percent weight in total steam supply). This insensitiveness results in almost constant houseload and ejector's motive steam consumptions. In the operation of GPP X, the NCG content is only 35% of its design, while the daily generation fluctuates below the base-load according to grid regulator instructions. This dynamic operation provides an opportunity for energy efficiency efforts through modification of the ejector system and cooling circulation pump to be more adaptive to changes in load, which ultimately supports conservation of steam reserves. Performance analysis and design of control systems for ejectors and circulating cooling water pumps are the scopes of the thesis discussion that performs option evaluation, which includes: regulating cooling water rate, controlling motive steam flow, or the combination of both, and also physical modification of the ejector.